Genetic Diversity and Population Structure Analysis of Tropical Soybean (Glycine max (L.) Merrill) using Single Nucleotide Polymorphic Markers (Global Journal of Science Frontier Research, 2020)
Soybean (Glycine max (L.) Merrill) is among the most important crops worldwide due to its numerous uses in feed, food, biofuel, and significant atmospheric nitrogen fixation capability. To understand the genetic diversity and population structure of tropical soybean germplasm, 89 genotypes from diverse sources were analyzed using 7,962 SNP markers. The AMOVA results showed low diversity among and high within the populations, while the polymorphism information content (PIC) was 0.27. Both phylogenetic and principal component analysis grouped the 89 soybean genotypes into three major clusters, while population structure grouped the soybean genotypes into two subpopulations. On the other, the average Roger genetic distances within the study population was 0.34. The low diversity reported in the studied soybean germplasm pool is particularly worrying, considering the new trends of climate change and the emergence of new pests and diseases of soybean. Therefore, in order to address these challenges and develop soybean varieties with desirable traits, there is a need to broaden the genetic base of tropical soybean through the importation of germplasm from other countries.
Keywords: genetic diversity; population structure; single nucleotide polymorphism (SNP); soybean; tropical soybean genotypes